AGING IN PLACE: THE REALITIES OF OLDER HOMELESS WOMEN NAVIGATING URBAN STREETS AND SHELTERS. (20th December 2022) - Gonyea, Judith; O'Donnell, Arden
Abstract: Older homeless women have often been an invisible population; however, this is changing as their numbers grow. Today, women age 50 and older represent 30% of the shelter population. In this qualitative study, we explored the question, What does "aging in place" mean to women in their fifties who are navigating the urban streets and shelter system?" Our study's purpose was to gain a deeper understanding of the impacts of daily displacement and migration and, through the women's accounts, engage in a critical analysis of the shelter system's practices and policies. Fifteen older chronically homeless women were recruited via a flyer posted at a city's women's day shelter to participate in an onsite interview about their homelessness experiences. Using a phenomenological approach, in depth semi-structured interviews were conducted, recorded and transcribed verbatim. Our analysis process was inductive and iterative with the culminating phases being theme generation and interpretation. Participants identified challenges centered on six themes: 1) loss of a sense of control, self-determination, and independence, 2) lack of physical security, 3) worsening physical and emotional health, 4) lack of comfort, familiarity, and routine, 5) weakening or loss of social connections, and 6) a diminished sense of self-worth. The findings highlight the links between place, sense of belonging, and identity. The data underscored that shelters were dehumanizing places that further diminished women's sense of self. We discuss reforms needed to disrupt shelter and housing systems' practices that further disempower and stigmatize the women and fail to support pathways out of homelessness.